Aprendizagem com mobilidade na perspectiva dialógica: reflexões e possibilidades para práticas pedagógicas - Graziola Júnior, Paulo Gaspar (Universidade do Vale do Rio do Sinos, 2009)
We are living a moment of profound transformations in society, from the use of digital technologies on the most varied domains that involve our everyday life. Concerning Education, traditional teaching and learning theories are insufficient to help us understand how subjects are developed in a highly technological world, and it favors the appearing of new theories and methodologies that provide teaching and learning with the use of different digital technological means to promote human development. With this, there is an increasing need of people’s mobility, of access and information exchange in any time and space, of ideas, experiences and knowledge sharing besides the necessity to amplify the traditional spaces of formal education, favor the use of the emergent mobile learning (m-learning), supported by the use of wireless mobile technologies (WMTs), such as Personal Digital Assistant (PDAs), palmtops, smart phones, cell phones, among others. It is in this context that a appears the problem that was the sta
Keywords: colaboração; cooperação; diálogo; práticas pedagógicas; aprendizagem com mobilidade; collaboration; cooperation; dialog; teaching practices; mobile learning; Ciências Humanas